Antibacterial and mechanical properties of pit and fissure sealants containing zinc oxide and calcium fluoride nanoparticles - Dara Lakshmi Swetha; C Vinay; K S Uloopi; Kakarla Sri RojaRamya; Rayala Chandrasekhar (Wolters Kluwer Medknow Publications, 2019)
Context: Pit and fissure sealants (PFSs) are the most effective preventive materials in dentistry. Secondary caries around the sealed pits and fissures at the material-tooth interface and the wear of the material remains the common problems. To address these problems, efforts have been made by incorporating zinc oxide (ZnO) and calcium fluoride (CaF2) nanoparticles (NPs) into the sealants to develop caries-inhibiting and stress-bearing sealants. Aim: Evaluation of antibacterial and mechanical properties of PFS containing ZnO and CaF2 NPs. Settings and Design: This was an in vitro study. Materials and Methods: A total of 196 fissure sealant samples were divided into six test groups and a control group. The test group samples were prepared by incorporating two concentrations (0.5 wt% and 1 wt%) of ZnO and CaF2 NPs into the sealants. The antibacterial activity was evaluated by direct contact test; compressive and flexural strengths were evaluated by a universal testing machine. Statistical Analysis Used: Statistical analysis was done by one-way ANOVA and post hoc Tukey test. Results: Sealants containing 1 wt% ZnO and CaF2 NPs and their mixture exhibited significantly higher antibacterial activity against Streptococcus mutans and Lactobacillus acidophilus when compared to control group (P < 0.001). Samples with ZnO NPs exhibited similar mechanical properties as conventional sealant (control group); however, the samples with CaF2 NPs showed inferior mechanical properties (P < 0.05). Conclusion: The observations of the study infer that sealants containing 1 wt% ZnO and CaF2 NPs and their mixture exhibited superior antibacterial activity. The mechanical properties of samples containing ZnO and mixture of ZnO and CaF2 particles remained comparable to the conventional sealants.